PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM UPAYA MENINGKATKAN DISIPLIN KERJA GURU PADA SDIT KARTIKA BUANA BOJA KENDAL - Salafudin, Umi Bariroh; Wahid, Abdul; Salafudin, Moh Anwar (STKIP Pesisir Selatan, 2025)
This study aims to analyze the role of school principal leadership in improving teachers' work discipline at SDIT Kartika Buana Boja Kendal. Effective leadership plays a crucial role in creating a conducive work environment and enhancing teacher performance. This research employs a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. The research subjects consist of the school principal, teachers, and administrative staff. Data analysis follows the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that the school principal acts as an educator, manager, administrator, supervisor, leader, and motivator. The principal enforces discipline through strict supervision, sanctions, and rewards for outstanding teachers. Furthermore, the leadership strategies implemented successfully enhance teachers' professionalism and sense of responsibility in performing their duties. This study provides insights into the effectiveness of school principal leadership in improving teachers' work discipline through a holistic approach. It also emphasizes the importance of balancing firmness with a motivational approach to enhance educators' discipline.